An Ideology of Minister of Religion’s Speech in Social Media (Tik Tok And Youtube): A Critical Discourse Analysis - Ulya Maulani Subhan; Roni Subhan (Journal of ELT, Linguistics, and Literature, 2025)
This study aims to analyze the ideology embedded in the Minister of Religion’s speech as presented on social media platforms, particularly TikTok and YouTube, through the framework of Critical Discourse Analysis (CDA). The research employs the models of CDA Teun van Dijk to examine three interrelated dimensions: textual, social cognition, and contextual. Data were collected from selected videos and transcripts of the Minister’s speeches that discuss moral, social, and religious issues. The analysis reveals that the Minister’s language reflects an ideology of moderation, unity, and moral awareness within the context of Indonesia’s multicultural society. At the textual level, the speeches use persuasive, inclusive, and moral expressions that emphasize the importance of tolerance and spirituality. The social cognition analysis indicates that the Minister’s beliefs and values are strongly influenced by Islamic moderation (wasathiyah) and national harmony. Meanwhile, the contextual analysis shows that the discourse serves as a medium to shape public ideology, promoting religion as a constructive and modern force within social life. Overall, the findings demonstrate that social media has become a strategic platform for the dissemination of religious ideology, where language functions as a tool for shaping public perception, moral identity, and social cohesion